Roundtable Technique and its Correlation with EFL Preparatory School Students' Achievement in Writing Hortatory Exposition Text (Journal of Humanities and Social Sciences Research, 2023)
Foreign language instruction methodologies vary, and there is no universally best technique for teaching English as a foreign language. The effectiveness of using the Roundtable Technique for teaching Hortatory Exposition Text (HET) to preparatory school students is investigated in this study. The research aims to assess the students' achievement in writing HET, determine differences between the experimental and control groups, and compare achievement levels at the recognition and production levels. The hypotheses related to the students' achievement and group differences are tested. A sample of seventy-seven fifth-year scientific female students, randomly divided into experimental and control groups, is taught the same material over eight weeks. The obtained results reveal a significant difference in achievement levels in favor of the experimental group, as well as a significant difference between the recognition and production levels. The study concludes with key findings and recommendations for further research.